2013
DOI: 10.1063/1.4836576
|View full text |Cite
|
Sign up to set email alerts
|

Metal-insulator transition in SrTi1−xVxO3 thin films

Abstract: x ≤ 1) thin films with thicknesses of ∼ 16 nm were grown on (001)-oriented LSAT substrates using the pulsed electron-beam deposition technique. The transport study revealed a temperature driven metal-insulator transition (MIT) at 95 K for the film with x = 0.67. The films with higher vanadium concentration (x >0.67) were metallic, and the electrical resistivity followed the T 2 law corresponding to a Fermi liquid system. In the insulating region of x <0.67, the temperature dependence of electrical resistivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 33 publications
4
23
0
Order By: Relevance
“…The observed trends in variation of electrical conductivity in the high‐temperature range are in agreement with the literature data on the low‐temperature resistivity measurements. It has been reported that the electrical resistivity in SrV 1− y Ti y O 3− δ system at T ≤300 K decreases with increasing V content, whereas the metal–insulator transition was observed at y ≈0.3–0.4 . One may expect, therefore, that the composition with y= 0.5 should undergo metal–semiconductor transition between room temperature and 340 °C.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The observed trends in variation of electrical conductivity in the high‐temperature range are in agreement with the literature data on the low‐temperature resistivity measurements. It has been reported that the electrical resistivity in SrV 1− y Ti y O 3− δ system at T ≤300 K decreases with increasing V content, whereas the metal–insulator transition was observed at y ≈0.3–0.4 . One may expect, therefore, that the composition with y= 0.5 should undergo metal–semiconductor transition between room temperature and 340 °C.…”
Section: Resultsmentioning
confidence: 99%
“…[68][69][70][71] On the other hand, Ti 4 + cations have no de lectrons, and stoichiometric SrTiO 3 is aw ide-bandgap semiconductor. [50] The substitution of Vb yT ir esults in ap erturbation of the conduction band, a gradualn arrowing of the effective bandwidth, and, eventually, localization of electronic charge carriers [49][50][51] accompanied by a decreaseintheir concentration. As aresult, the Ti-rich solid solutions demonstrate semiconducting behavior with the electronic transport contributed, most likely,b ye lectron hopping between V 4 + /V 3 + pairs.…”
Section: Electrical Properties Under Reducing Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…State of the art SVO thin‐films grown by pulsed laser deposition (PLD) onto SrTiO 3 (STO) (100) have a RRR of 2.4, which is much lower compared to hybrid‐MBE deposition technique ,. Since PLD is a most common technique for complex oxides, process conditions to perform an efficient SVO thin‐film are taken under strong interest ,,. In this regard, oxygen is particularly known as a crucial parameter leading for instance to the creation of a Metal Insulator Transition (MIT) in other perovskite compounds for STO, and LaNiO 3 ,,.…”
Section: Introductionmentioning
confidence: 99%